1992
DOI: 10.1128/iai.60.9.3845-3851.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Candida albicans oligomannosidic epitopes by using monoclonal antibodies

Abstract: Six monoclonal antibodies (MAbs) from various laboratory sources (EB-CA1, EB-CA2, H5, AF1, C6, and 5B2), reacting with the polysaccharidic moieties of Candida albicans mannoproteins, were used for epitope mapping by an enzyme-linked immunosorbent assay (ELISA) with neoglycolipids and by Western blotting (immunoblotting) of a C. albicans germ tube extract. The ELISA involved neoglycolipids constructed from three families of oligomannosides released by sequential depolymerization of C. albicans phosphopeptidoman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 35 publications
5
56
0
Order By: Relevance
“…The Candida mannan has long been recognized for its antigenic properties [2^4]. We have con¢rmed the reactivity of MAb EB-CA1 with NGLs constructed with mannan acid stable oligomannosides [14], and shown that within this pool of oligomannose residues, the length of the oligomannoside chain was a limiting factor for recognition. A minimal number of ¢ve mannose residues was required for binding.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The Candida mannan has long been recognized for its antigenic properties [2^4]. We have con¢rmed the reactivity of MAb EB-CA1 with NGLs constructed with mannan acid stable oligomannosides [14], and shown that within this pool of oligomannose residues, the length of the oligomannoside chain was a limiting factor for recognition. A minimal number of ¢ve mannose residues was required for binding.…”
Section: Discussionmentioning
confidence: 92%
“…The sequential depolymerization of the mannan has been previously described [14]. The ¢rst step consisted of a mild acid hydrolysis: 500 mg mannan was dissolved in 10 mM HCl and heated for 30 min at 100³C.…”
Section: Depolymerization Of the Mannanmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported the presence of three kinds of b-1,2 linkage-containing side chains in the mannans from Candida species [11][12][13][14][15][16][17]. Because the b-1,2-linked mannose unit is present among the pathogenic fungi only in the mannan of the genus Candida and the b-1,2 linkage-containing side chains behave as strong antigens, many workers [18][19][20][21][22][23][24][25] have produced monoclonal antibodies to b-1,2-linked mannose units to protect against candidiasis, for the serodiagnosis of candidiasis, or for the identification of mechanisms of Candida infection. Furthermore, studies have indicated the b-1,2-linked mannose units participate in the adherence of Candida cells to mammalian cells as the first step in infection [26][27][28].…”
mentioning
confidence: 99%